La relevancia de los amicus curiae en los arbitrajes internacionales de inversión pos COVID-19 en materia de salud pública - Carbajal Valenzuela, Christian (2021)
To reduce the spread of the COVID-19 virus, States have been taking various measures to safeguard public health and other interests of their populations, actions that are not exempt from criticism, some will be considered necessary and reasonable, adopted in accordance with the state regulatory powers provided for by International Law. Others, on the other hand, because they might be considered arbitrary, disproportionate, and discriminatory, will be understood as violating International Investment Law and specific standards contained in Investment Treaties. Probably, in relation to many of these measures, the most discordant voices will be those of foreign investors, who may consider their interests severely harmed.Because of this situation of collision between legal regimes and interests protection of public health vs. protection of foreign investment, this article explores how amicus curiae, in times of emergency such as the one we are experiencing, will be of particular relevance to the issuance of reasonable decisions by arbitral tribunals in the forthcoming international investment arbitrations concerning public health. If the appropriate participation of amicus curiae in procedures with a clear public interest involved is consolidated, it will be an element that will contribute fundamentally to the implementation of transparency mechanisms in the investor-state dispute settlement system, which is absolutely necessary for its legitimacy.